The Legal Status of Digital Wills as Objects of Notarial Deeds within the National Legal System - Putu Bagus Arya Krisna; Ni Luh Made Mahendrawati; I Nyoman Alit Puspadma (Inovasi Pratama Internasional. Ltd, 2026)
The development of information technology has changed how individuals express, store, and prove their final testamentary intention. In the Indonesian national legal system, this development raises a concrete legal issue because the Civil Code still places wills within strict testamentary formalities, while the Electronic Information and Transactions Law recognizes electronic information and electronic documents as lawful evidence. This article examines the position of digital wills as objects of notarial deeds in the national legal system by focusing on two issues: the validity of wills in digital form and the authority of notaries to receive digital wills for deposit. This research uses normative legal research with statutory and conceptual approaches. The analysis shows that a digital will, including a voice recording, cannot independently be treated as a valid will because it does not yet satisfy the formal requirements of Indonesian civil inheritance law. Nevertheless, a voice recording may serve as evidence of animus testandi if its authenticity, integrity, time of creation, and connection with the testator can be proven. A notary may receive a digital medium as an object of deposit and may formalize the testator's intention into an authentic deed, but may not legalize the digital recording as a new form of will outside the law. The article argues that the safest construction is to position digital records as sources of testamentary intention, not as substitutes for notarial deeds.